Prevalent Misconceptions and Determinants of Knowledge in Patients with Diabetes Mellitus in a Medical College - Shah, S.V.A.; Roy, P.; Ansari, F. (Journal of Diabetes and Endocrinology Association of Nepal, 2021)
Background: Diabetes prevalence is high in South Asian countries. In Nepal, numbers are increasing every year. Many patients are aware that they have diabetes only when they develop one of its complications. This study was done to assess the knowledge and awareness of diabetes mellitus and the prevailing myths in outpatients of a tertiary care hospital.Method: It is a cross-sectional study conducted on diabetic patients attending the Department of Endocrine and Internal medicine, Nobel Medical College, over two months using questionnaires.Results: Among 200 diabetics, 67% believed that insulin is the medication of the last stage, 76% said insulin once started cannot be stopped.37% said medicine once started cannot be stopped. There was a misconception regarding the use of COVID-19 vaccines. 27% of the respondent opinioned that COVID-19 vaccines cause harm to diabetic patients.Conclusion: The survey showed many myths and misconceptions are prevailing in society regarding diabetes which needs to be addressed for better patient outcomes. The age of the participants, duration of illness, and their education status did not correlate with the total score for prevailing myths in the Nepalese population.